Reformation og deformation - Widmann, Peter (Dansk Teologisk Tidsskrift, 2010)
The aim of the Reformation movement was to overcome the destructive developments of the Western Catholic Church, not to establish a different Church or independent communities. The Reformers, however, were from the beginning confronted with the charge of deforming rather than reforming the Church, and this led to the split of Western Christianity and the emergence of Protestantism. The development of Protestantism was driven by different attempts to renew Christianity but the outcome thereof was often criticised as a destruction of the entire Christian tradition. The Protestant theology of the 20th century in the wake of Karl Barth regarded itself as opposed to two deformations, one represented by Roman Catholicism, another by “neo-protestantism” respectively. This makes it clear that the threat of Christianity’s deformation cannot be overcome by turning back to something original but demands a quest for new Christian realizations.